The monthly changes of chloroplast pigments content in selected plant species exposed to cement dust pollution - Saravana Kumar R; D, Sarala Thambavani (Journal of Research in Biology, 2011)
Chloroplast pigments were shown to be very sensitive to various environmental influences. Changes in chlorophyll and carotenoid content were investigated in selected plant species exposed to alkaline dust emitted by the cement industry. Pigments were extracted consequently for 30, 60, 90, 120, 150 and 180 days interval and quantified spectrophotometrically. In comparison with control site all measured pigments were reduced in dust-exposed plant species. This is due to deceleration of the biosynthetic processes rather than degradation of pigments. Chlorophyll b content appeared to be more sensitive than chlorophyll a in polluted plants. Total carotenoids needed a longer period of time to reach nearly the same level as in controls. The progression of pigment decline in polluted sites appeared not to be dramatically accelerated. It might thus be concluded that polluted sites had sufficient biosynthetic capacity to prevent irreversible damage by cement dust